2021
DOI: 10.1124/jpet.120.000337
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antimuscarinic Antidepressant-like Compounds with Reduced Effects on Cognition

Abstract: The cholinergic nervous system has been implicated in mood disorders, evident in the fast-onset antidepressant effects of scopolamine, a potent muscarinic antagonist, in clinical studies. One prominent disadvantage to the use of scopolamine in the treatment of depression is its detrimental effects on cognition, especially as such effects might aggravate cognitive deficits that occur with depression itself. Thus, the identification of antimuscarinic drugs that are free of such detrimental effects may provide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…1, bottom, closed circles). The muscarinic antagonist, L 687 306 (Freedman et al ., 1992; Winger et al ., 2020; Johnson et al ., 2021) antagonized the discriminative stimulus effects of arecoline (Fig. 1, top, open squares) and to a lesser degree relieved the rate-suppressing effects of arecoline (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, bottom, closed circles). The muscarinic antagonist, L 687 306 (Freedman et al ., 1992; Winger et al ., 2020; Johnson et al ., 2021) antagonized the discriminative stimulus effects of arecoline (Fig. 1, top, open squares) and to a lesser degree relieved the rate-suppressing effects of arecoline (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rats were trained to report the discriminative stimulus effects of 1.0 mg/kg s.c. arecoline by responding on one lever following administration of arecoline and to respond on another lever following administration of saline. The fundamental muscarinic effects of arecoline in this assay were established initially by evaluating the effects of a muscarinic antagonist, L 687 306 (Freedman et al ., 1992; Freedman et al ., 1993; Winger et al ., 2020; Johnson et al ., 2021), as well as two nicotinic antagonists on the discriminative stimulus effects of arecoline. Subsequently, the ability of nicotine to produce an arecoline stimulus was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from studies on scopolamine, there has been little published on muscarinic antagonists as potential antidepressants. In the past year, Johnson et al [ 291 ] reported the development of two potential lead compounds (L-687306 and CJ2100, Figure 8 ) targeting the orthosteric site acting as rapid-acting antidepressants that lack cognitive deficits. Additionally, L-687306 was synthesized and evaluated as a possible treatment of AD in the early 1990s by Merck [ 292 , 293 , 294 ] to identify a more selective mAChR agonist with reduced efficacy (hence reduced cholinergic side-effect profile), and CJ2100 is a cyclopropyl oxadiazole derivative of arecoline.…”
Section: Drug Design Targeting the Machrs: Major Depressive Disordermentioning
confidence: 99%
“…* p < 0.05, ** p < 0.01, *** p < 0.001, **** p < 0.0001. Reproduced with permission from Johnson CR et al [ 291 ].…”
Section: Figurementioning
confidence: 99%
“…Hence, current data-sharing platforms for conventional behavioral data lack information on standardization decreasing the potential for re-use of data. The development of computerized and automated behavioral testing is a game-changing opportunity in cognitive behavioral data collection and analysis [13][14][15][16][17] . Touchscreen technology 18 has enabled the automation of multiple high-level cognitive tests and the generation of data in digital formats that lend themselves to deposition in FAIR-compliant data repositories.…”
Section: Introductionmentioning
confidence: 99%